1977
DOI: 10.1111/j.1365-3059.1977.tb01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of White Rot of Onion (Sclerotium cepivarum) by Coniothyrium minitans

Abstract: SUMMARY The fungus Coniothyrium minitans is pathogenic to Sclerotium cepivorum, the causal agent of white rot of onion. In a glasshouse experiment, pycnidial dust prepared from C. minitans was used in soil treatments and as a seed dressing to protect onion seeds sown in S. cepivorum infested soil. Comparison was made with seed dressed with calomel, the standard fungicide used for white rot control. Seed dressing with C. minitans or soil dusting with C. minitans protected the onion plants from white rot as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
3

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 5 publications
0
23
1
3
Order By: Relevance
“…C. minitans filmcoating of seed naturally infected by S. sclerotiorum needs to be examined. This contrasts with experiments where application of C. minitans conidia to onion seeds using methyl cellulose sticker gave control of Allium white rot (Sclerotium cepivorum) equivalent to that provided by the then current chemical treatment with calomel (mercurous chloride) (Ahmed & Tribe, 1977). It has been suggested that inoculum potential of the pathogen might be the key to biocontrol (Adams, 1990;Huang, 1992;Deacon & Berry, 1993).…”
Section: Discussioncontrasting
confidence: 42%
“…C. minitans filmcoating of seed naturally infected by S. sclerotiorum needs to be examined. This contrasts with experiments where application of C. minitans conidia to onion seeds using methyl cellulose sticker gave control of Allium white rot (Sclerotium cepivorum) equivalent to that provided by the then current chemical treatment with calomel (mercurous chloride) (Ahmed & Tribe, 1977). It has been suggested that inoculum potential of the pathogen might be the key to biocontrol (Adams, 1990;Huang, 1992;Deacon & Berry, 1993).…”
Section: Discussioncontrasting
confidence: 42%
“…Coniothyrium mini tans Campbell, a known parasite of fungal sclerotia, has been shown to protect onion plants from S. cepivorum to the same extent as fungicide seed dressing with calomel in glasshouse trials (Ahmed & Tribe 1977). Other reported antagonists of S. cepivorum include Gliocladium roseum Bainier which inhibits the formation of sclerotia and parasitises mycelia and a number of Penicillium species which have been shown to inhibit the growth of S. cepivorum mycelium in vitro, producing inhibition zones (Ghaffar 1969;Utkhede & Rahe 1980).…”
Section: Received 4 February 1988; Accepted 3 August 1988mentioning
confidence: 99%
“…In the same country, other workers found potential in Coniothyrium minitans for control of white rot equal to that provided by calomel, without the phyto-and environmental toxicity associated with that chemical's use (Ahmed and Tribe, 1977). Research in Canada has also suggested Bacillus subtilis and Penicillium nigricans may provide protection from white rot up to the level shown by industry standard fungicides like iprodione and vinclozolin (Utkhede and Rahe, 1980).…”
Section: Biological Control Of White Rotmentioning
confidence: 91%